2022
DOI: 10.3390/antiox11020359
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Melatonin and Nitrogen Improve Drought Tolerance of Maize Seedlings by Regulating Growth and Physiochemical Attributes

Abstract: Melatonin plays an important role in numerous vital life processes of animals and has recently captured the interests of plant biologists because of its potent role in plants. As well as its possible contribution to photoperiodic processes, melatonin is believed to act as a growth regulator and/or as a direct free radical scavenger/indirect antioxidant. However, identifying a precise concentration of melatonin with an optimum nitrogen level for a particular application method to improve plant growth requires i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 52 publications
(88 reference statements)
3
30
0
Order By: Relevance
“…The 0.05 mM EBR was sprayed on plants every three days. For WW plants, the moisture content was retained at a field capacity (FC) of 80%, whereas 60% FC for DS was based on daily measurement of pot weight [ 37 ]. Drought stress was applied to plants for 24 days.…”
Section: Methodsmentioning
confidence: 99%
“…The 0.05 mM EBR was sprayed on plants every three days. For WW plants, the moisture content was retained at a field capacity (FC) of 80%, whereas 60% FC for DS was based on daily measurement of pot weight [ 37 ]. Drought stress was applied to plants for 24 days.…”
Section: Methodsmentioning
confidence: 99%
“…Grassi and Magnani, (2005) found that adequate N content partially restored the photosynthetic biochemistry compared to limited N availability. Previous studies have reported that when the drought stress level intensifies, it reduces the leaf area, which subsequently affects photosynthetic pigmentation and reduces stomatal conductance and transpiration rate ( Ahmad et al, 2022 ). In this manner, supporting the plant’s water status and stomatal opening under high N is important to maintaining the conductance of leaf to CO 2 , photosynthetic responses, and electron transfer ( Liu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has diverse functions in plant growth, development, and biotic and abiotic stress responses [ 9 , 10 , 46 , 47 , 48 , 49 ] by modulating the cellular redox balance [ 50 , 51 , 52 ] and protein quality control [ 53 ]. Additionally, melatonin functions in concert with other plant hormones during growth and under stressful conditions [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%